INTEGRATED EDUCATION ON NAPZA, HIV/AIDS, AND MENTAL HEALTH TO FOSTER HEALTHY AND WELL-CHARACTERIZED ADOLESCENTS - Melda Rumia Rosmery Simorangkir; Hotmaulina Sihotang; Bernadetha Nadeak; Eustalia Wigunawati; Eva Hertina Pardede; Dian Kristin N Manulang (International Journal of Multidisciplinary Reseach, 2026)
Adolescents are a vulnerable population facing various risk behaviors, including the abuse of narcotics, psychotropic substances, and other addictive substances (NAPZA), HIV/AIDS transmission due to limited reproductive health knowledge, and mental health problems that may affect character development and overall quality of life. These challenges highlight the importance of integrated educational interventions as a preventive strategy to improve adolescents' health literacy. This Community Service Program (Pengabdian kepada Masyarakat/PKM) aimed to enhance adolescents' knowledge of the dangers of substance abuse, HIV/AIDS prevention, and the importance of maintaining mental health, while fostering positive attitudes and healthy behaviors through a church-based community approach. The program was conducted at HKBP Duren Jaya Bekasi and involved 60 adolescents attending catechism classes. The activities employed interactive health education, group discussions, case studies, question-and-answer sessions, and evaluations using pre-tests and post-tests. The results indicated that participants gained a better understanding of the dangers of substance abuse, HIV/AIDS prevention, the importance of mental health, and the adoption of healthy and responsible lifestyles. Furthermore, the church-based educational approach encouraged active participation and strengthened positive character values in addressing various challenges faced by adolescents. The program demonstrates that collaboration between higher education institutions and churches is an effective strategy for improving health literacy while fostering healthy, resilient, and well-characterized adolescents.